Unveiling the antibacterial potential of biodiesel derived from waste cooking oil - Mat Rosid, Sarina; Mat Rosid, Salmiah Jamal; Mohd Shohaimi, Norshahidatul Akmar; Ibrahim, Siti Fadhilah (GADING Journal of Science and Technology, 2024)
Biodiesel can be made from waste materials such as used cooking oil. Each year, approximately 540,000 tons of waste cooking oil (WCO) are discarded in Malaysia without being treated as waste. However, WCO has been identified as one of the most suitable and well-known sources of biodiesel. Therefore, the goal of this research was to use WCO to produce biodiesel via the transesterification method. Due to its low cost and mild reaction conditions, transesterification is a common method. The functional group in produced biodiesel and WCO was identified using FTIR, and the antibacterial properties of yielded biodiesel were evaluated using the Kirby-Bauer test or zone of inhibition test. According to the Kirby-Bauer method, the bacteria will be inoculated onto a solid growth medium, and antibiotic discs will be introduced to the plate. This technique is used to see if pathogenic bacteria become sensitive or resistant to antimicrobial compounds found in the biodiesel sample. The FTIR results confirmed the existence of the functional group of fatty acid methyl ester (FAME) compounds in the produced biodiesel. With an inhibition zone of 8 mm, the biodiesel produced exhibited antibacterial properties. This demonstrated that the biodiesel components produced have antibacterial properties. These findings show that biodiesel derived from used cooking oil has the potential to be investigated further as antibacterial agents and to improve its performance when replacing the fossil fuels.